Maximal Covering Problem Model (MCP) for Fire Station Location Determination: A Case Study in Al-Khoms City - Abubakr Abdusalam Milad; Anwr Mohamed Hmdan Alhdar (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
The study addressed the distribution of fire stations in Al-Khoms city, Libya, using a mathematical model for the maximal coverage problem to achieve optimal service coverage with the least number of stations. The model focuses on determining the optimal locations for stations, taking into account the population density and risk levels of the site, and providing a rapid response not exceeding 15 minutes. The study used the simplex method to determine four optimal stations in the areas (Kaam, Al-Khoms power station, Al-Khoms seaport and Ghanima). The results showed improved coverage and reduced 2 stations from the open stations, which are Soq Al-Khames station and Al-Khoms city station. The study recommends establishing a new station in Ghanima, improving roads to support response speed, using GIS systems and updating data continuously. In areas similar to the case study, the model is applicable to achieve the best use of resources.